ANALISIS PENGARUH FAKTOR MODAL, KEMAMPUAN DAN LOKASI USAHA TERHADAP KEBERHASILAN UKM PADA PUSAT OLEH-OLEH KHAS BENGKULU - Eti Arini; Heldi Sahputra; M. Galy Nyoman (UM. Bengkulu, 2020)
The purpose of this research is to determine the effect of capital, ability and business location on the success of SMEs at the center of souvenirs typical of Bengkulu. This research is a quantitative descriptive research. The samples in this study were 28 typical Bengkulu business owners who were located in Soekarno-Hatta street Anggut Atas Village, Ratu Samban District, Bengkulu City. The results of multiple linear regression tests show that capital has a significant effect on the success of SMEs (tcount= 3.375 and Sig = 0.001), ability has a significant effect on the success of SMEs (tcount = 1.567 and Sig = 0.009), and business location has an effect on the success of SMEs (tcount = 3.861 and Sig = 0.002). Key word: Capital, Skill, Business Location, SMEs